Multifunctional, Novel Formulation for Repairing Photoaged and Sun-Damaged Skin: Insights from In Vitro, Ex Vivo, and In Vivo Studies - María Moneo-Sánchez; Nagore de Pablo; Leire Arana-Pascual; Itziar Beitia; Sandra Benito-Cid; Raúl Pérez-González (Cosmetics)
Prolonged sun exposure disrupts the skin’s structural, mechanical, and functional properties, accelerating aging and contributing to skin disorders. To counteract these effects, we developed a formulation containing potent antioxidant, anti-inflammatory, moisturizing, and reparative ingredients to protect and repair sun-damaged skin. The efficacy of the formulation was evaluated through in vitro, ex vivo, and in vivo studies. Results demonstrated that the formulation reduced oxidative stress and suppressed the production of pro-inflammatory cytokines interleukin-6 (IL-6) and interleukin-8 (IL-8), as well as lactate dehydrogenase (LDH) secretion, in a photodamaged skin model, nearly reaching levels observed in undamaged skin. It also restored collagen levels, improving structural integrity. In vivo, no adverse reactions were observed when used for 28 or 56 days. The formulation improved skin hydration by up to 46%, reduced transepidermal water loss by 20%, increased luminosity by 70%, and reduced hyperpigmented spots by 14%. It also enhanced skin firmness and elasticity by 30% and reduced wrinkle volume and density by up to 53% and 19%, respectively. These findings demonstrate that the formulation’s active ingredients effectively target the pathways altered by UV exposure, offering considerable potential for preventing and reversing sun-induced skin damage while improving both the appearance and functionality of the skin.